Regulatory T Cell in Kidney Transplant: The Future of Cell Therapy? - Ahmad Matarneh; Meet Patel; Kinna Parikh; Amanda Karasinski; Gurwant Kaur; Vaqar Shah; Nasrollah Ghahramani; Naman Trivedi (Antibodies, 2025)
The long-term use of immunosuppressive drugs following kidney transplantation increases the risk of life-threatening infections, malignancies, and, paradoxically, eventual allograft rejection. Therefore, achieving a balance between over-immunosuppression and under-immunosuppression is critical to optimizing patient outcomes. One promising approach is immune cell-based therapy using suppressor immune cells to modulate the immune response more precisely. Among these, regulatory T cells (Tregs) are the most extensively studied and have shown significant potential in the post-transplant setting. Tregs are broadly categorized into thymus-derived and peripherally derived subsets. Physiologically, they play key roles in maintaining immune tolerance, including in autoimmune diseases and within the tumor microenvironment. Their immunosuppressive functions are mediated through both contact-dependent and contact-independent mechanisms. Studies investigating the use of Tregs following kidney transplantation have shown encouraging results. This review summarizes the biology of Tregs and highlights current evidence supporting their role in transplant immunotherapy.